Chapter State of the Art of Magnetic Gears, their Design, and Characteristics with Respect to EV Application - Fodorean, Daniel (InTechOpen, 2016)
This chapter briefly explains the advantage of using magnetic gears (MGs) for transportation applications. Usually, a traction EV unit consists of, besides the engine or motor, a mechanical gear. The drawbacks of using mechanical gears have been emphasized, especially with respect to high-speed motorization, where high transmission ratio can be reached only by connecting multiple gears in series. A magnetic gear is capable of overcoming these issues. The chapter presents a state of the art on the available MGs, with fixed or variable transmission ratio, pointing out their applicability. Next, the possible design approaches (harmonic, magnetic reluctance equivalent circuit, and vector potential) are introduced. Furthermore, the output performances (power and torque) of two types of studied MGs are evaluated, with emphasis on the main loss criteria: iron losses in all the active parts of the MG. Finally, the influence of several materials is observed by means of numerical computation in order to decide, based on specific configuration, the most suited variant for transportation and aeronautic applications.